Comparison of Distally Based Sural Fasciocutaneous Island Flap with a nd without Inclusion of Sural Nerve - Tabish Samuel; Shahid Hameed; Abdul Majid; Shahid Hussain Naqvi; Shah Faisal; Farman Mehmood (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To compare the inclusion and exclusion of the sural nerve in fascio-cutaneous flap repair for lower extremity reconstruction in terms of flap survival, flap size, recovery of skin sensation and complications.